Mapping of mitogen and metabolic sensitivity in organoids defines requirements for human hepatocyte growth - Hendriks, Delilah; Artegiani, Benedetta; Margaritis, Thanasis; Zoutendijk, Iris; Chuva de Sousa Lopes, Susana; Clevers, Hans (Nature Research, 2024)
Mechanisms underlying human hepatocyte growth in development and regeneration are incompletely understood. In vitro, human fetal hepatocytes (FH) can be robustly grown as organoids, while adult primary human hepatocyte (PHH) organoids remain difficult to expand, suggesting different growth requirements between fetal and adult hepatocytes. Here, we characterize hepatocyte organoid outgrowth using temporal transcriptomic and phenotypic approaches. FHs initiate reciprocal transcriptional programs involving increased proliferation and repressed lipid metabolism upon initiation of organoid growth. We exploit these insights to design maturation conditions for FH organoids, resulting in acquisition of mature hepatocyte morphological traits and increased expression of functional markers. During PHH organoid outgrowth in the same culture condition as for FHs, the adult transcriptomes initially mimic the fetal transcriptomic signatures, but PHHs rapidly acquire disbalanced proliferation-lipid metabolism dynamics, resulting in steatosis and halted organoid growth. IL6 supplementation, as emerged from the fetal dataset, and simultaneous activation of the metabolic regulator FXR, prevents steatosis and promotes PHH proliferation, resulting in improved expansion of the derived organoids. Single-cell RNA sequencing analyses reveal preservation of their fetal and adult hepatocyte identities in the respective organoid cultures. Our findings uncover mitogen requirements and metabolic differences determining proliferation of hepatocytes changing from development to adulthood.
Keywords: General Chemistry; General Biochemistry,Genetics and Molecular Biology; General Physics and Astronomy